A new living contract: cases in the implementation of the Living Wage by British SME retailers. Issue 6 (2nd October 2017) - Werner, Andrea; Lim, Ming
Abstract : Purpose: The purpose of this paper is to provide evidence for the motivations of SMEs for introducing the Living Wage (LW), focussing on retail as one specific sector. It develops understanding of the strategic benefits and challenges these employers face in balancing financial, ethical and social considerations in small businesses. Design/methodology/approach: The study employed mixed methods: a survey and semi-structured interviews. The interviews are presented as part of three case studies. Findings: Findings indicate that employers were, for the most part, motivated by personal ethics and beliefs about fair wages and social justice. They suggest that SME accrue benefits from LW accreditation such as reputational benefits and higher employee morale, but that there are also potential pitfalls of LW adoption related to pay structure and incentives. The sustainability of the LW emerged as an issue in terms of the long-term strategy and brand positioning of the companies involved. Research limitations/implications: The nature of the research was exploratory and thus the study only allows for limited generalisation. Recommended avenues for further research include gathering data from different levels of organisations and from different stakeholders. Originality/value: This is the first paper to investigate the drivers for, and implementation of, the LW in SMEs. The specific characteristics of SMEs – their ethos, low visibility, reliance on trusting relationships and limited resources, among others – make the study of why and how they choose to implement the LW very interesting. This study is the first to gather and analyse data from SME retailers and wholesalers that have implemented the LW.